P16/INK4a and KI-67 Evaluation of Intraepithelial and Benign Cervical Lesions at the University College Hospital, Ibadan - A Retrospective Immunohistochemically Study - Adetona A. E; Ogun G. O; Okolo C. A.; Ogunbiyi J. O (Journal of Cancer Genetics And Biomarkers, 2017)
Objective P16INK4a and Ki-67 are adjuncts to current histological assessment of cervical biopsies in identifying cases that require strict follow up and prompt intervention. This study aimed to evaluate P16INK4a and Ki-67 expression in squamous intraepithelial and other benign cervical lesions. Methods A retrospective cross-sectional study of 153 cases of cervical biopsies diagnosed as CIN and benign cervical lesions between 2006 and 2013 at the University College Hospital, Ibadan, Nigeria. Slides and tissue blocks of all the selected cases were retrieved and classified using the 2003 WHO classification for intraepithelial and benign cervical lesions and were stained with p16INK4a and Ki-67 immunohistochemical stains following heat-induced antigen retrieval. Results were evaluated and compared with histologic diagnosis. Results Cases were classified as chronic cervicitis (12.3%), squamous Metaplasia (0.7%), CIN 1 (47.1%), CIN 2 (36.6%) and CIN 3 (3.3%). Majority of the non-dysplastic cervical lesions (including chronic cervicitis cases) showed low P16INK4a reactivity. Positive P16INK4a reactivity was seen in 80% of CIN 3 cases, 83.9% of CIN 2 cases, and, surprisingly, in 97.2% of CIN 1 cases. Ki-67 positivity was seen in 36.6% of cases (75% CIN 2 and 60% CIN 3). There was a significant correlation between the H&E diagnoses of CIN and P16INK4a/Ki-67 immunoreactivities. Conclusion Majority of the CIN 1 cases showing low grade p16INK4a immunereactivity strongly suggesting that cervical squamous intraepithelial neoplasia in this environment is likely associated with high grade HPV subtype infections and may predict possible progression to high grade squamous intraepithelial neoplasia. The use of P16INK4a and Ki-67 in the evaluation of cervical biopsies for benign mimics of high grade intraepithelial lesion will aid proper single Pathologist evaluation and help in patients triaging for follow up.
Keywords: p16